Validity and reliability of the Berlin questionnaire for the detection of moderate or severe obstructive sleep apnea in patients aged 40 years or older detected from primary care - Navarrete-Martínez, Esther; Muñoz-Gómez, Rafaela; Serrano-Merino, Jesús; Perula-de Torres, Luis Angel; Vaquero-Abellán, Manuel; Silva-Gil, Fátima; Roldán-Villalobos, Ana; Martín-Rioboó, Enrique; Ruiz-Moruno, Javier; Romero-Rodríguez, Esperanza; González-Lama, Jesús; Montes-Redondo, Gertrudis (Frontiers in Medicine, 2023)
The Obstructive Sleep Apnea syndrome (OSA) is a highly prevalent condition. In Spain and other countries, only 5-9% of patients with OSA have been diagnosed and treated. The lack of accessibility to diagnosis is considered the main cause of this situation through easy-to-use screening instruments, it is necessary to check their validity and reliability in the context where they are to be used.Objective: To validate the Spanish translation of the Berlin Questionnaire for screening for moderate or severe OSA in patients aged 40 years or more detected in Primary Care.A descriptive observational study, with a first qualitative phase of transcultural adaptation to Spanish using the translation-back-translation method. Setting: Primary Care Level of the Spanish National Health System. A total of 255 patients recruited from 7 healthcare centers completed the study. The Berlin questionnaire was administered to the recruited patients, and subsequently, a respiratory polygraphy was performed to confirm the diagnosis of OSA. The concurrent criterion validity of the questionnaire and its reliability in terms of internal consistency and reproducibility (intra-observer agreement) were analyzed.The patients' mean age was 54.76 years (SD: 6.57; 95%CI: 53.53-54.99), and 54.12% were men (95%CI: 47.96-60.27). We found that 61.57% (95%CI: 55.57-67.57) presented OSA (apneahypopnea index -AHI->5), and 45.5% (95%CI: 17.05-57.92) presented moderate or severe (AHI>15) OSA. The Berlin questionnaire, with a cut-off point of 4.5, showed a sensitivity of 76.77% (95%CI: 67.94-85.59), a specificity of 74.49% (95%CI: 65.35-83.63), a positive predictive value of 75.25% (95%CI: 66.34-84.16), a negative predictive value of 76.04% (95%CI: 66.98-85.10), and an area under the curve of 0.786 (95%CI:0.721-0.851). Cronbach's alpha coefficient was 0.730 (95%CI: 0.668-0.784), and the Kappa index was 0.739 (95%CI: 0.384-1.000).The Spanish adaptation of the Berlin questionnaire has good validity and reliability as a test for the diagnostic screening of moderate or severe OSA in patients aged 40 years or older. The findings of our study confirm that primary care physicians should use such screening tools to predict OSA.